2017
DOI: 10.1111/1365-2435.12814
|View full text |Cite
|
Sign up to set email alerts
|

Bill size mediates behavioural thermoregulation in birds

Abstract: Summary Bird bills have been the subject of classic evolutionary studies that demonstrate how morphological adaptations are driven by foraging ecology. As significant areas of heat loss, bills are also under selection with respect to thermoregulation, yet the ecological consequences of this function have been largely ignored until recently. Given the role of bills in thermoregulation is important, we predict that birds should behave to minimise heat loss through their bills at lower ambient temperatures by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
64
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(67 citation statements)
references
References 49 publications
(74 reference statements)
2
64
1
Order By: Relevance
“…These results both fit with our prediction that birds found in colder climates should be more likely to use these behaviours. Many of the species at higher latitudes have smaller bills and legs (Nudds & Oswald, ; Symonds & Tattersall, ), emphasising the role that ambient temperature may play in determining use of back rest, standing on one leg and sitting (Bouchard & Anderson, ; Brodsky & Weatherhead, ; Reebs, ; Ryeland et al, ; Wellmann & Downs, ). We cannot entirely rule out the possibility that our observed pattern is due to species in temperate latitudes being more well‐studied (there are more temperate than tropical species in our analysis).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These results both fit with our prediction that birds found in colder climates should be more likely to use these behaviours. Many of the species at higher latitudes have smaller bills and legs (Nudds & Oswald, ; Symonds & Tattersall, ), emphasising the role that ambient temperature may play in determining use of back rest, standing on one leg and sitting (Bouchard & Anderson, ; Brodsky & Weatherhead, ; Reebs, ; Ryeland et al, ; Wellmann & Downs, ). We cannot entirely rule out the possibility that our observed pattern is due to species in temperate latitudes being more well‐studied (there are more temperate than tropical species in our analysis).…”
Section: Discussionmentioning
confidence: 99%
“…Given the thermoregulatory nature of the behaviours, we predicted that birds found in colder climates (e.g., higher latitudes and altitudes) would be more likely to have been observed using these behaviours. This prediction derives from the existing observations within species that the use of these behaviours increases in colder conditions (Anderson & Williams, ; Brodsky & Weatherhead, ; Ryeland et al, ; Wellmann & Downs, ).…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…Among the sexually dimorphic tidal marsh species, this is perhaps easier, as multiple studies across a large diversity of bird taxa have reported positive correlations between minimum winter temperatures and bill size (Snow 1954, Symonds and Tattersall 2010, but see VanderWerf 2012, Friedman et al 2017, Ryeland et al 2017. Among the sexually dimorphic tidal marsh species, this is perhaps easier, as multiple studies across a large diversity of bird taxa have reported positive correlations between minimum winter temperatures and bill size (Snow 1954, Symonds and Tattersall 2010, but see VanderWerf 2012, Friedman et al 2017, Ryeland et al 2017.…”
Section: The Case For Sexual Selectionmentioning
confidence: 99%